Pupils’ Ideas about Urinary and Endocrine System - Kubiatko, Milan (Scientia in educatione, 2017)
The aim of the study was to survey lower secondary school pupils’ understanding of endocrine and urinary system. The pilot study was carried out among 78 respondents and the main research was carried out among 204 respondents. The contour of human body drawn on an A4-size paper was used as a research tool, with the students being asked to fill in the required information. Another aim was to determine the influence of selected variables like gender, school location (village vs. town), year of study, presence of a doctor in the family and the pupil’s perception of his or her own health. The analysis of variance was used as statistical method. The pupils tended to add drawings of urinary system organs more frequently than those of the endocrine system. The variables with significant influence on the results were gender, year of study, school location and the pupil’s perception of his or her own health.